METODOLOGI TAFSIR AL-MISHBAH - Suharyat, Yayat; Asiah, Siti (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
Interpretation al-Mishbah is a great work of Indonesian children. Muhammad Quraish Shihab through the interpretation of al-Mishbah aims to present the verses of the Qur'an so that it is easily accessible to readers. Mufassir tries to explain to trace the Qur'an or the content of its verses so that the messages of the Qur'an are applied wholeheartedly in personal and community life. This paper attempts to discuss the background of the mufassir's life, the limits of interpretation, and the methodology of al-Mishbah's interpretation. The results of this paper explain that the experience of M. Quraish Shihab examines the previous verses of the Qur'an when he was a mature lecturer in writing the interpretation of al-Mishbah. Interpretation al-Mishbah is written in simple language and can be reached by various groups and in accordance with the purpose of writing, namely grounding the Qur'an. Judging from the method, namely the tahlily method, this is illustrated verse by verse according to the order of the letters contained in the Mushaf. While the pattern is al-adabi al ijtima'i, namely the style of interpretation which is in the aspects of literature, culture and society.ABSTRAKTafsir al-Mishbah merupakan sebuah karya besar anak bangsa Indonesia. Muhammad Quraish Shihab lewat tafsir al-Mishbah bertujuan menghidangkan ayat-ayat al-Qur’an agar mudah dipahami pembacanya. Mufassir berusaha untuk menjelaskan untuk menghapus kesalahpahaman terhadap al-Qur’an atau kandungan ayat-ayatnya sehingga pesan-pesan al-Qur’an diterapkan dengan sepenuh hati dalam kehidupan pribadi dan masyarakat. Makalah ini berusaha membahas bagaimana latar belakang kehidupan mufassir, penafsiran tafsir, dan metodologi tafsir al-Mishbah. Hasil dari makalah ini menjelaskan bahwa pengalaman M. Quraish Shihab menafsirkan ayat-ayat al-Qur’an sebelumnya pada saat menjadi dosen membuatnya matang dalam menulis tafsir al Mishbah. Tafsir al-Mishbah ditulis dalam bahasa yang sederhana dan dapat dipahami oleh berbagai kalangan dan sesuai dengan tujuan penulisannya yaitu membumikan al-Qur’an. Dilihat dari metode penafsirannya yaitu metode tahlily, ini tergambar dari menafsirkan ayat demi ayat sesuai urutan surat yang terdapat dalam Mushaf. Sedangkan corak penafsirannya adalah al-adabi al ijtima’i, yaitu corak tafsir yang menekankan pada aspek sastra, budaya dan kemasyarakatan.